Protocolo para prática clínica da terapia fotodinâmica em endodontia: avaliação da qualidade do guideline por meio do instrumento Agree II - Lopes, Camila Basilio (2021)
Parameters such as wavelength, energy, application time and number of sessions can vary according to the problem and the characteristics of the procedure and the patient. It is necessary to provide information with scientific evidence in an accessible way to the clinician who is not familiar with analyzing evidence of academic works. In this context, the proposal of the present project is the elaboration of the recommendation synthesis of clinical protocols for the use of photodynamic therapy in endodontics in permanent teeth. For this purpose, high methodological quality protocols will be identified based on systematic literature search and quality assessment using the validated instrument, Appraisal of Guidelines Research & Evaluation Instrument (AGREE-II). Following the identification of the studies, a synthesis of the recommendations of the studied procedures was carried out. The synthesis was submitted to a group of experts for evaluation and adaptation in a consensus process using the Delphi methodology. Analysis of the literature on the application of aPDT in endodontics has shown that clinical trials with good levels of evidence and clinical recommendation are available, with two studies classified as A1A of clinical recommendation and level A of evidence. The writing of the protocol reached a satisfactory level and an appropriate content validity index after the second round of evaluation by the expert judges. The studies included in this research showed a predominantly explanatory level, demonstrating the need for pragmatic designs to increase the degree of clinical applicability.